PERLINDUNGAN HUKUM BAGI ANAK PELAKU TINDAK PIDAN (Studi Putusan Pengadilan Negeri Medan Nomor: 27/Pid.Sus-Anak/2014/PN.Mdn) - Khairul Anwar Hasibuan; Marlina Marlina; Muhammad Eka Putra; Edy Ikhsan (Universitas Sumatera Utara, 2016)
ABSTRACT Indonesia as a State Party in theConvention on the Rights of the Child governing the principle of legal protection for the child is obliged to provide special protection to children in conflict with the law. One of the forms of child protection is realized through special criminal justice system for children in conflict with the law. This is confirmed in the United Nations Standard Minimum Rules for the Administration of Juvenile Justice.The findings show that, the first is the legal protection of children as perpetrators of criminal acts is indispensable because it is useful for: 1) Children are not stablephysically and mentally, 2) To ensure the children freed from inhuman or demeaningpunishment, 3 ) To ensure the independence of the child, so as not seized unlawfully or arbitrarily, 4) To ensure that the criminal (penalty) applies only as an ultimumremedium; the second is the legal protection should be given to the child is the legal protection that covers several concepts as follows: 1) The concept of Restorative Justice; and 2) Concept of Diversy. The third isthe child criminal liability based on the judge's decision are as follows: Accepting an appeal from lawyer and public prosecutor of the child; strengthening decision of Medan District Court No.:27/Pid.SUS.Anak/2014/PN.Mdn; Establish the length of children detained entirely deducted from the sentence imposed; Ordered the child remains in custody; Charge a second child in the case of judicial level, which is in the level of appeal for Rp.2.500,00 (Two thousand five hundred rupiahs). Keywords : Legal Protection , Responsibility , Children Actors Crime.